The relationship between sweat chloride levels and mortality in cystic fibrosis varies by individual genotype - Espel, Julia C.; Palac, Hannah L.; Bharat, Ankit; Cullina, Joanne; Prickett, Michelle; Sala, Marc; McColley, Susanna A.; Jain, Manu (Journal of cystic fibrosis, 2018)
The association between CFTR genotype, sweat chloride and mortality has been inconsistent, but no previous analyses have examined the association stratified by individual genotypes. To evaluate the genotype-specific association between sweat chloride and mortality. The CFF Patient Registry was assessed and included all patients in the registry between 1996 and 2012 with at least one F508del allele. We excluded patients without a documented genotype or plausible sweat chloride level. The primary outcome was time to mortality during the observation period. We examined 15 genotypes using the three most prevalent alleles in each of 5 classes. We compared subgroups of sweat chloride using Kaplan-Meier curves, log-rank tests, and multivariable Cox PH models. The overall predictive value of sweat chloride on mortality was assessed using area under the receiver operating characteristic curves. 18,893 subjects met inclusion criteria. Sweat chloride distribution was similar across genotypes in patients with class 1 mutations, but was significantly different across genotypes in mutation classes 2–5. The R117H/F508del genotype patients demonstrated an association between sweat chloride and mortality (HR: 1.32 for every 10mmol/L increase in sweat chloride [95% CI 1.12–1.54]. There were also significant associations in patients with F508del/F508del, I507del/F508del, G551D/F508del and 2789+5G→A/F508del genotypes, though the clinical relevance for these genotypes is unclear. There is significant variability in sweat chloride distribution across CFTR class 2–5 genotypes. The relationship between sweat chloride and mortality varies by genotype with a relatively strong relationship in R117H/F508del patients.